Pelatihan Software Akuntansi Accurate SMK Nusantara 1 Ciputat - Farhan Ady Pratama; Arry Eksandy; Rudi Harianto (Prisani Cendekia, 2023)
Accounting Information Systems is learning material that can be used to face the world of work, so that it becomes an additional skill that is very useful for SMK students. One of the Community Service (Pengmas) activities carried out by Pembangunan Jaya University is targeted at school partners. Community Service this time was carried out at SMK Nusantara 1 Ciputat, community service activities were carried out offline and it is hoped that this will open up further collaboration between UPJ and SMK Nusantara 1 Ciputat